2014
DOI: 10.3354/cr01227
|View full text |Cite
|
Sign up to set email alerts
|

The decline of Norwegian kittiwake populations: modelling the role of ocean warming

Abstract: The black-legged kittiwake Rissa tridactyla is a pelagic seabird whose population has recently declined in most parts of the North Atlantic and which is red-listed in most bordering countries. To investigate a possible cause for this decline, we analysed the population dynamics of 5 kittiwake colonies along the Norwegian coast, ranging from 62° to 71°N, over the last 20 to 35 yr. By quantifying the importance of sea surface temperatures (SST) in relevant areas of the North Atlantic, we tested the importance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…Kittiwake populations declined rapidly in the 1990s throughout most of the species’ breeding range, corroborating results of previous studies at local scales (Frederiksen, Wanless, Harris, Rothery, & Wilson, ; Labansen, Merkel, Boertmann, & Nyeland, ; Sandvik et al., ). Changes in kittiwake population trends tracked changes in trends of spring SST around the colonies and when the ocean warming was faster, the decline in kittiwake colony size was steeper.…”
Section: Discussionsupporting
confidence: 87%
“…Kittiwake populations declined rapidly in the 1990s throughout most of the species’ breeding range, corroborating results of previous studies at local scales (Frederiksen, Wanless, Harris, Rothery, & Wilson, ; Labansen, Merkel, Boertmann, & Nyeland, ; Sandvik et al., ). Changes in kittiwake population trends tracked changes in trends of spring SST around the colonies and when the ocean warming was faster, the decline in kittiwake colony size was steeper.…”
Section: Discussionsupporting
confidence: 87%
“…Jenouvrier et al (2005a) found that climate may have a direct or a lagged effect on population dynamics depending on environmental stochastic conditions. Some studies showed that climate have a simultaneous effects both direct and lagged because each demographic parameter are affected differently by climate Sandvik et al, 2014). Finally, the existence of non-linear relationships between climate and seabird ecological parameters has seldom been explored (e.g., Durant et al, 2004;Jenouvrier et al, 2005a;Ballerini et al, 2009;Regular et al, 2009), despite the importance of identifying tipping points and thresholds when buffering capacity (i.e., both behavioral and demographic) is overcome.…”
Section: The Mechanisms Linking Climate Variation To Seabird Populatimentioning
confidence: 99%
“…NAO can explain variation in some different ecological variables in some species, but not in others (e.g. : Saetre et al, 1999;Forchhammer et al, 2002;Durant et al, 2004;Sandvik et al, 2005;Saether et al, 2009;Dippner et al, 2014;Sandvik et al, 2014). These studies and others illustrate the fact that NAO can be highly relevant for some variables and species; but an association may not mean causation.…”
Section: Discussionmentioning
confidence: 97%
“…where β i represents the slope of the ith environmental covariate X i ; ε, environmental noise, i.e., an independent variable with zero mean and variance σ 2 e ; N t , population size in year t; r, long-term intrinsic population growth rate; σ 2 d , demographic variance; X i,t , environmental covariate i in year t. The parameters β i , r, and σ 2 e were estimated using maximum likelihood (for details, see Saether et al, 2009;Sandvik et al, 2014), while σ 2 d was assumed to be 0.1, which is a realistic value for long-lived birds (Lande et al, 2003). To ensure that the latter assumption did not critically affect the results, different values of σ 2 d were tested; varying σ 2 d tenfold (0.01-1) changed the estimate of β by less than 2%.…”
Section: Population Modelingmentioning
confidence: 99%